Letter from S.R. Bond to Margaret C. Booth - Bond, S. R. (1894)
S.R. Bond, Attorney-at-Law, writes to Margaret M. Booth née Cardeza to report the success of the relief bill which will be sent to the President of the United States for his signature.
Keywords: Booth, James Curtis, 1810-1888; Bills, Legislative; Martinez Cardeza, Margaret; Mint of the United States; United States Mint